Analysis of resistance criteria of modified building mortars to various influences - G. V. Nesvetaev; G. N. Hadzhishalapov; I. A. Zhivotkova (Вестник Дагестанского государственного технического университета: Технические науки)
Objective. The article deals with the analysis of the resistibility of building mortars made of dry building mixtures according to various criteria after 100 cycles of freezing and thawing and aging for 120 days according to the Russian National Standard 24544-2020Method. The investigation was based on standards to determine the parameters of the pore structure of hardened mortars, flexural and compressive strength, frost resistance, ultrasonic pulse velocity, dynamic modulus of elasticity, adhesion strength to a standard concrete base and frost resistance of the contact zone, and shrinkage deformations.Result. The relationships of changes in the investigated quality indicators of mortars under the specified impacts depending on the dosage of redispersible polymer powders and the type of mineral additive in the complex modifier are established. It is determined that long-term maturing to air-dry conditions can have more negative effect on some resistance criteria compared to 100 standard freeze-thaw cycles. The research reveals the relationships and offers the equations that describe the relationship between the criteria of "change in flexural strength", "change in adhesion strength to the concrete base" and the criterion of "change in compressive strength" taking into account the formulation factors and the type of mineral additive. The work points to inexpediency of usage such resistance criteria as "change in ultrasonic pulse velocity and dynamic modulus of elasticity" under the considered impacts. An approach to quantitative standardization of the criterion of "change in flexural strength" is proposed.Conclusion. When developing dry construction mixes, it is necessary to take into account the influence of recipe factors on the indicators that determine the resistance of solutions under various operational impacts. The most "rigid" criterion is the change in the bending strength limit. The influence of complex modifiers on the resistance criteria depends on the type and dosage of additives and can be opposite.